Study on copper electromigration reliability of the ULSI devices - Low, Joon Kiat. (2008)
This project studies copper electromigration reliability with the help of engineers of Chartered Semiconductor Mfg. Ltd. As the processing of the copper metallization can greatly affect its reliability, experiments will be conducted to determine how some of the processing conditions and environments can affect the performance of copper.